2020
DOI: 10.1039/c9ra10628f
|View full text |Cite
|
Sign up to set email alerts
|

DMAP-stabilized bis(silyl)silylenes as versatile synthons for organosilicon compounds

Abstract: DMAP-stabilized silylenes 1a–c, which are convenient, room temperature stable synthetic equivalents for the corresponding highly reactive free bis(silyl)silylenes are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…From the resulting monomeric silylene complexes, Si­(IV) hydrides can be obtained by the direct oxidative addition of H 2 , as outlined in Scheme , ,,, or via NH 3 activation . The donor-stabilized bis­(silyl)­silylenes R 3 Si­(R′ 3 Si)­Si·DMAP (R = t Bu, R′ = Me; 833 ; R = R′ = Si t Bu 2 Me; 834 ; R = R′ = Me; 835 ), react with 1 atm of H 2 at 65 °C to produce the corresponding dihydrosilanes 836 − 838 in quantitative yields, with loss of DMAP in each case . In a similar fashion, the amido­(silyl)­silylene {Me 3 Si­(Dipp)­N}­{(Me 3 Si) 3 Si}­Si: ( 839 ) and in situ generated (IPr=N)­{(Me 3 Si) 3 Si}­Si: ( 841 ) react with H 2 to give the silicon­(IV) dihydrides 840 and 842 (Scheme ).…”
Section: Molecular Hydrides Of the Group 14 Metals (Silicon Germanium...mentioning
confidence: 99%
See 1 more Smart Citation
“…From the resulting monomeric silylene complexes, Si­(IV) hydrides can be obtained by the direct oxidative addition of H 2 , as outlined in Scheme , ,,, or via NH 3 activation . The donor-stabilized bis­(silyl)­silylenes R 3 Si­(R′ 3 Si)­Si·DMAP (R = t Bu, R′ = Me; 833 ; R = R′ = Si t Bu 2 Me; 834 ; R = R′ = Me; 835 ), react with 1 atm of H 2 at 65 °C to produce the corresponding dihydrosilanes 836 − 838 in quantitative yields, with loss of DMAP in each case . In a similar fashion, the amido­(silyl)­silylene {Me 3 Si­(Dipp)­N}­{(Me 3 Si) 3 Si}­Si: ( 839 ) and in situ generated (IPr=N)­{(Me 3 Si) 3 Si}­Si: ( 841 ) react with H 2 to give the silicon­(IV) dihydrides 840 and 842 (Scheme ).…”
Section: Molecular Hydrides Of the Group 14 Metals (Silicon Germanium...mentioning
confidence: 99%
“…), acyclic silylenes with ligands based on the electropositive donor elements B or Si (i.e., boryl, -BR 2 , or silyl -SiR 3 groups) in conjunction with nitrogen-based ligands are often employed; such ligand combinations result in the small HOMO-LUMO energy gaps needed for small molecule activation. 975 From the resulting monomeric silylene complexes, Si(IV) hydrides can be obtained by the direct oxidative addition of H 2 , as outlined in Scheme 133, 67,69,1086,1087 or via NH 3 activation. 1088 The donor-stabilized bis(silyl)silylenes R 3 Si(R′ 3 Si)Si•DMAP (R = t Bu, R′ = Me; 833; R = R′ = Si t Bu 2 Me; 834; R = R′ = Me; 835), react with 1 atm of H 2 at 65 °C to produce the corresponding dihydrosilanes 836−838 in quantitative yields, with loss of DMAP in each case.…”
Section: Catalysis Mediated By Molecular Group 13 Hydridesmentioning
confidence: 99%
“…In 2020, it was reported that silylenes (R 2 Si:), the heavier congeners of carbenes, can also be used in cycloaddition reactions with ethylene. 45 The active species were stabilized with 4-(dimethylamino)pyridine (DMAP), and after the reaction, DMAP was easily isolated through precipitation. As a result, a series of siliranes was obtained (Scheme 12 ).…”
Section: (2+1) Cycloadditionmentioning
confidence: 99%
“…40,41 The reaction of 2 with 2,3-dimethylbutadiene at 60 °C provided (1 + 4) cycloadduct 5 (69% yield) and free IMe 4 , while this reaction did not proceed at room temperature. This result indicates that 2 serves as a surrogate of bis(trimethylsilyl)silylene, 42,43 although it is unclear whether 2 dissociates into bis(trimethylsilyl)silylene and IMe 4 in solution at 60 °C. In addition, 2 reacted with Me 3 SiI to provide silylimidazolium 3 (83% yield).…”
mentioning
confidence: 98%
“…The molecular structure of 4 obtained by single-crystal XRD analysis (Figure b) indicated that the Si1–C1 distance in 4 [1.9466(13) Å] is close to that in 2 [1.9354(11) Å] and Si1–B distance in 4 [2.1504(14) Å] is slightly longer than those of reported NHC-coordinated silylene-borane complexes [1.999–2.074 Å]. , The reaction of 2 with 2,3-dimethylbutadiene at 60 °C provided (1 + 4) cycloadduct 5 (69% yield) and free IMe 4 , while this reaction did not proceed at room temperature. This result indicates that 2 serves as a surrogate of bis­(trimethylsilyl)­silylene, , although it is unclear whether 2 dissociates into bis­(trimethylsilyl)­silylene and IMe 4 in solution at 60 °C. In addition, 2 reacted with Me 3 SiI to provide silylimidazolium 3 (83% yield).…”
mentioning
confidence: 99%